Associação da adubação biológica e química na cultura do milho - Salbego, Lourenço (2021)
Corn is one of the most cultivated plants in the world, in addition to playing a fundamental role in the Brazilian economy. The indiscriminate use of chemical fertilizers, pesticides, inadequate management practices, conventional planting, erosion, monoculture, among other practices, have left most Brazilian soils 'poor' from the biological point of view. The use of biofertilizers has become an alternative in improving the physical, chemical and biological conditions of the soil, bringing back 'life in the soil', which helps to reestablish its microbiome, favoring the development of the crop, in addition to the growing demand worldwide for healthier foods and good management practices that contribute to the reduction of the indiscriminate use of chemical inputs, the balance of the ecosystem and environmentally correct practices. The objective of this work was to evaluate the attributes of soil and plant in the corn crop, under treatment with chemical fertilization, and the treatment with chemical fertilization associated with biological, in the no-tillage system in the straw, in the experimental area of the Polytechnic College of UFSM in the 2018/2019 harvest. The use of the biofertilizer Microgeo® presented itself as an alternative to decrease chemical fertilization in cultivation over the years, and it was obtained associated with chemical fertilization, an increase in the weight of a thousand grains of 21.9% in relation to the control where only chemical fertilization was used. It is concluded that with the use of chemical fertilizer associated with biological fertilizer, a significant increase was obtained in all evaluated attributes, such as decreased soil density, increased root volume and length, ear size, plant height, stem thickness, number of grains per ear, number of rows of grains per ear and PMG (weight of a thousand grains).